LA SALUD ORAL DE LAS MUJERES GESTANTES, SUS REPERCUSIONES Y LOS ASPECTOS QUE INFLUENCIAN SU ATENCIÓN (2011)
The oral health in the pregnant is not good; the systemic and oral changes in the pregnant could affect the oral and general health and the life of the woman, the fetus and the new born. Several aspects affect the maternal oral health and the dental attention and they must be analyzed in integral way in order to changes and promote the health and the life of the woman in their vital cycle but especially during her pregnancy. The aim of this paper is to describe the changes that occur in a general context in pregnant women and oral, the effects on their health and that of his son, and the issues that affect their dental care.